Analysis of the production of photovoltaic facades integrated into the BIPV building (LACCEI, 2024)
In developing countries, there has been an increase in the use of building-integrated photovoltaic (BIPV) systems in recent years. This technology is relatively new in Latin America, unlike other European countries, and it has not had a great impact on the generation market in buildings. Its architectural flexibility, which allows the use of different types of colored solar cells, makes it attractive to improve energy efficiency. aesthetics of buildings and provide demand savings. Using photovoltaic systems integrated into a building envelope instead of traditional materials can contribute to the production of energy where it is consumed. Therefore, the objective of this work is to evaluate the energy production of different types of semitransparent solar panels. For this, the PVSite Photovoltaic Performance Analysis Program was used, a simulation tool for the integration of photovoltaic systems. The results show that in general, the last months of the year have lower production, while the maximum production is achieved in March with a semi-crystalline panel from the manufacturer Onyx X6 producing 673.85 kWh.